IN VITRO ROOTING AND ACCLIMATIZATION OF QUINCE SCIONS CVS. MC AND ADAMS, USED AS ROOTSTOCK FOR PEAR - ERIG, Alan Cristiano; SCHUCH, Márcia Wulff; CHAVES, Anderson da Costa (Scientia Agraria, 2004)
The objective of this work was to determine salts and sucrose concentration of the culture medium that favor the in vitro rooting of quince cvs. MC and Adams, and the substrate that it makes possible the largest survival of the scions in acclimatization. In the Experiment 1 they were studied the salts concentration of the MS culture medium (50, 75 and 100% of the original concentration) and the sucrose concentration in the medium (0, 15, 30 and 45 g.L-1), in the completely randomized experimental design, in factorial outline 3 x 4. To the 35 days were evaluated the rooting percentage, the number and the length of roots and the intensity of callus formation in the basis of the explants. In the Experiment 2, it was studied the substrate type (substrate Plantmax, Plantmax + vermiculite [mixture 1:1] and Plantmax + vermiculite + soil [mixture 1:1:1]), in the blocks at random experimental design. In this experiment the survival percentage was evaluated to the 10, 20 and 30 days of acclimatization, exposing the scions gradually the environmental conditions. The in vitro rooting of the cvs. MC and Adams was favored with the reduction of the salts of the MS medium to 75% of it original concentration, and with 15 g.L-1 of sucrose in the culture medium. In spite of none of the substrate it was previously sterilized, just the substrate that contained soil in the mixture presented total death of the scions already to the ten days of acclimatization, caused by rottenness in the lap of the plant. The substrate Plantmax and the mixture Plantmax + vermiculite made possible the largest survival of the scions in the acclimatization.